(untitled) (Journal of Hama University, 2026)
Abstract: This study examines the role of royal alliances in Strengthening Castilian influence during the reign of Alfonso VIII and Eleanor of England. It analyzes the political, diplomatic, and strategic dimensions of their union in 1170, which marked a significant connection between Castile and England in the medieval period. The research highlights the importance of Alfonso VIII’s minority, during which noble families like the Lara sought to consolidate power and influence at court. Eleanor’s marriage not only strengthened Castile’s internal stability but also secured a vital international alliance. By tracing negotiations, marriage settlements, and diplomatic correspondence, the study shows how the English royal family strategically extended its influence in the Iberian Peninsula. The alliance affected territorial disputes, particularly with Navarre, and provided Castile with a broader European political network. Moreover, the marriage set a precedent for future dynastic diplomacy, with Alfonso VIII and Eleanor arranging subsequent strategic marriages for their children to consolidate power and reinforce political legitimacy. This research underscores that such alliances were not mere family arrangements but integral tools for political positioning, diplomacy, and transnational influence in medieval Europe. The findings demonstrate how the Castilian monarchy leveraged marital ties to strengthen its sovereignty, expand its influence, and engage in European geopolitics, creating enduring Anglo-Castilian connections that shaped the Iberian Peninsula’s history well into the 13th century.